'Screw‐in' tendency of rotary nickel–titanium files due to design geometry. (12th September 2014) - Ha, J. H.; Cheung, G. S. P.; Versluis, A.; Lee, C. J.; Kwak, S. W.; Kim, H. C.
Abstract Aim To examine the effect of several standard geometric characteristics of rotary instruments on the 'screw‐in' forces and stresses generated on root dentine using 3D finite element analysis (FEA). Methodology Four cross‐sectional designs (triangular, slender‐rectangular, rectangular and square) were evaluated. The area of the triangular cross‐section and of the slender‐rectangular model were the same. Another rectangular model had the same centre‐core diameter as the triangular one. Each design was twisted into a file model with 5, 10 or 15 threads over its 16‐mm‐long working section. Three curved root canals were simulated as rigid surface models: θ = 15 degrees/R = 36 mm radius; θ = 30/R = 18; and θ = 45/R = 12. A commercial FEA package was used to simulate the file rotating in the canal to determine the 'screw‐in' force and reaction torque on the instrument. Results Instruments of a square cross‐section had the highest 'screw‐in' force and reaction torsional stresses followed by the rectangle, the triangle design and the slender‐rectangle design, respectively. The file with closer pitch generated lower stresses, compared with that with longer pitch. The greater the root canal curvature, the higher the 'screw‐in' force and reaction torque generated. Conclusion This study demonstrated that the 'screw‐in' tendency depends on both the instrument geometry and canal curvature. Clinicians should be aware that certain instrument designs are prone to develop high 'screw‐in' forces, requiring the operator to maintain control of the handpiece or to use a brushing action to prevent instruments being pulled into the canal.